Zur Stellung und Funktion des Hörverstehens im sprachpraktischen Unterricht polnischer Germanistikstudenten - Myczko, Kazimiera (Wydawnictwo Naukowe UAM, 1991)
The position of listening (oral comprehension) at German studies and the functions which it performs in the teaching process are determined by the level of foreign language mastery of the students. This level makes it that developing of a complex ability of oral comprehension, thus oriented to the reception of the meaning contained in the text, is connected in the course of teaching with developing of the other language skills and with the work on the subsystems of the language and in particular on the lexical subsystem. The general remarks contained in the first part of the article are in the course of further considerations the basis for differentiation of the position and functions of listening skill (oral comprehension) in specific years of studies.